Doing Gender Well and Differently in Dirty Work: The Case of Exotic Dancing. Issue 3 (4th August 2011) - Mavin, Sharon; Grandy, Gina
<x xml:space="preserve">Abstract</x> This article explores how a group of exotic dancers do gender and manage the stigma associated with their work and identities. We draw upon stigma management strategies from the dirty work literature and illuminate the doing of gender in these strategies. We also contribute to the debate that gender can be done well and differently through simultaneous, multiple enactments of femininity and masculinity. We consider the experiences of 21 exotic dancers working in a chain of UK exotic dancing clubs and conclude that in order to be good at their job, exotic dancers are expected to do gender well, that is, perform exaggerated expressions of femininity. However, we also theorize that for some dirty workers, specifically exotic dancers as sex workers, doing gender well will not be enough to reposition bad girls (bad, dirty work) into good girls (good, clean work). Finally, we propose that doing gender well will have different consequences in different types of work, thereby extending our findings to other dirty work occupations and organizations in general.